2014
DOI: 10.1161/hypertensionaha.114.03545
|View full text |Cite|
|
Sign up to set email alerts
|

Ambient Air Pollution and Pregnancy-Induced Hypertensive Disorders

Abstract: Gestational hypertension and preeclampsia are the most common complications of pregnancy affecting 2% to 10% of pregnancies after 20 weeks of pregnancy. 6,7 Gestational hypertension is usually diagnosed based on a systolic blood pressure of ≥140 mm Hg or a diastolic blood pressure of ≥90 mm Hg in previously normotensive women. 7 Preeclampsia is characterized by hypertension and protein in the urine. 6,8 In addition to maternal mortality, preeclampsia and related conditions are a leading cause of maternal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
188
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(194 citation statements)
references
References 41 publications
4
188
1
1
Order By: Relevance
“…Our findings are consistent with the results of 2 previous meta-analyses that summarized the associations between air pollution exposure during pregnancy and pregnancy-induced hypertensive disorders. 35, 36 Pedersen et al found that pregnancy-induced hypertensive disorders were significantly associated with a 5 μg/m 3 increment in PM 2.5 (OR=1.57; 95% CI: 1.26-1.96), a 10-μg/ m 3 increment in NO 2 (OR=1.20; 95% CI: 1.00-1.44), and a 10 μg/m 3 increment in PM 10 (OR=1.13; 95% CI: 1.02-1.26).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the results of 2 previous meta-analyses that summarized the associations between air pollution exposure during pregnancy and pregnancy-induced hypertensive disorders. 35, 36 Pedersen et al found that pregnancy-induced hypertensive disorders were significantly associated with a 5 μg/m 3 increment in PM 2.5 (OR=1.57; 95% CI: 1.26-1.96), a 10-μg/ m 3 increment in NO 2 (OR=1.20; 95% CI: 1.00-1.44), and a 10 μg/m 3 increment in PM 10 (OR=1.13; 95% CI: 1.02-1.26).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 2 recent metaanalyses suggest heterogeneity in the association between air pollution and various pregnancy hypertensive disorders (10,11), among which gestational hypertension (GH) is common but has received less research attention. Specifically, given that only 3 (12)(13)(14) of 17 studies in one meta-analysis (10) reported specific data on GH, no synthesis could be derived for this outcome separately. Furthermore, several important methodological issues preclude firm conclusions from the previous data.…”
mentioning
confidence: 99%
“…First, 16 of the 17 studies included in the meta-analysis by Pedersen et al (10) used birth certificate data, which often do not allow separation of GH from other subtypes of hypertensive disorders during pregnancy, as opposed to medical records and/or hospital discharge data. Second, all 3 studies on air pollution and GH as a separate outcome are singlecity based (12)(13)(14), if not from a single hospital (12), which potentially limits exposure contrasts (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, predisposing cardiovascular or metabolic risks for endothelial dysfunction, as part of an enhanced systemic inflammatory response, might dominate in the origin of late onset PE. Meta-analyses of epidemiological studies investigating the association between exposure to ambient air pollution and pregnancy-induced hypertensive disorders including gestational hypertension and PE report that exposure to air pollution (in particular nitrogen oxides and particulate matter) increases the risk of HDP [3]. The HELLP syndrome is a pregnancy-specific disease characterized by hemolysis (due to microangiopathic hemolytic anemia), elevated lactate dehydrogenase (LDH), elevated liver enzymes caused by acute liver damage, and a platelet count decreased by the enhanced consumption [4].…”
Section: Introductionmentioning
confidence: 99%